Ciglitazone inhibits growth and induces apoptosis in human colorectal cancer cell lines independently of PPARγ - Darus, Halisa Mohd; Yaacob, Nik Soriani; Nor, Norazmi Mohd (Penerbit Universiti Sains Malaysia, 2004)
The nuclear hormone receptor peroxisome proliferator-activated receptor (PPAR) γ is a ligand-activated transcription factor that regulates several biological processes such as adipogenesis, glucose homeostasis and cell growth.